2016
DOI: 10.1007/s11682-016-9616-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface-based morphometry reveals caudate subnuclear structural damage in patients with premotor Huntington disease

Abstract: In patients with premotor Huntington’s disease (pmHD), literature has reported decreases in caudate volume. However, the regional vulnerability of the caudate nucleus to pmHD remains to be clarified. We aimed to determine whether regional structural damage of the caudate nucleus was present in pmHD and was correlated with clinical profile using a surface-based morphometric technique applied to T1-weighted MRI. The study cohort consisted of 14 volunteers with genetically confirmed pmHD (6 males; 41.8 ± 13.2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(60 reference statements)
3
5
0
Order By: Relevance
“…The mean hippocampal volume did not differ between pmHD patients (M=3295+/−424) and controls (M=3346+/−371 mm^3), p=.8, d=.13. Shape analysis of these structures in the same sample was previously reported and revealed volume reductions from controls in the dorsal and medial portions of the caudate head (Kim et al, 2016). …”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The mean hippocampal volume did not differ between pmHD patients (M=3295+/−424) and controls (M=3346+/−371 mm^3), p=.8, d=.13. Shape analysis of these structures in the same sample was previously reported and revealed volume reductions from controls in the dorsal and medial portions of the caudate head (Kim et al, 2016). …”
Section: Resultssupporting
confidence: 66%
“…To increase the automated segmentation accuracy, which can be compromised by modeling of anatomic variability, each individual image to segment was registered to images in previously described template libraries, in which 50 caudates (Kim et al, 2016) and 368 hippocampi (Kim et al, 2012) were manually labeled on these template images. These images were taken from a database comprising healthy subjects, and patients with various brain disorders and presumably have good coverage of shape variability.…”
Section: Methodsmentioning
confidence: 99%
“…329 In a study from our center of 13 patients with pmHD and 13 age and gender-matched controls, smaller caudate volume combined with quantitative phase measurements on 7T MRI GRE sequences improved the prediction of time to disease onset (disease burden score). 331 Surface-based morphometry with 3T MRI in pmHD subjects with executive dysfunction has shown evidence of anteromedial paraventricular caudate atrophy, supporting prior neuropathological studies, 332,333 and indicating that this imaging measurement may be useful as a very early disease biomarker. In manifest (motor) stages of HD, structural MRI typically demonstrates global volume loss throughout the cerebrum, basal ganglia, brainstem, and cerebellum, 334 though the caudate, putamen, nucleus accumbens, and amygdala remain the most atrophic.…”
Section: Multiple System Atrophysupporting
confidence: 59%
“…The TFC scale assesses daily tasks performance while UHDRS‐TMS is a clinical rating scale assessing multiple domains of motor disability (Huntington Study Group, ; Reilmann & Schubert, ). In this regard, despite previous cross‐sectional studies indicating that caudate volume decrease mainly correlates with cognitive outcomes (Harris et al, ; Kim et al, ; Rosas et al, ), other studies have reported that it also correlates with the TFC status (Rosas et al, ; Tabrizi et al, ), suggesting its influence on functionality for daily living performance. In regard to the correlation with the UHDRS‐TMS decline, cross‐sectional studies have showed that the caudate volume decrease not only correlates with the global UHDRS‐TMS score (Coppen et al, ; Galvez et al, ; Padowski et al, ; Domínguez et al, , ), but also with specific domains of this scale, including chorea degree and eye movements’ deficits (Coppen et al, ; Galvez et al, ).…”
Section: Discussionmentioning
confidence: 89%